Modular and Stepwise Synthesis of a Hybrid Metal–Organic Framework for Efficient Electrocatalytic Oxygen Evolution - Shen, Jian-Qiang; Liao, Pei-Qin; Zhou, Dong-Dong; He, Chun-Ting; Wu, Jun-Xi; Zhang, Wei-Xiong; Zhang, Jie-Peng; Chen, Xiao-Ming (Journal of the American Chemical Society, 2017)
The paddle-wheel type cluster Co2(RCOO)4(LT)2 (R = substituent group, LT = terminal ligand), possessing unusual metal coordination geometry compared with other cobalt compounds, may display high catalytic activity but is highly unstable especially in water. Here, we show that with judicious considerations of the host/guest geometries and modular synthetic strategies, the labile dicobalt clusters can be immobilized and stabilized in a metal–organic framework (MOF) as coordinative guests. The Fe(na)4(LT) fragment in the MOF [{Fe3(μ3-O)(bdc)3}4{Fe(na)4(LT)}3] (H2bdc = 1,4-benzenedicaboxylic acid, Hna = nicotinic acid) can be removed to give [{Fe3(μ3-O)(bdc)3}4] with a unique framework connectivity possessing suitable distribution of open metal sites for binding the dicobalt cluster in the form of Co2(na)4(LT)2. After two-step, single-crystal to single-crystal, postsynthetic modifications, a thermal-, water-, and alkaline-stable MOF [{Fe3(μ3-O)(bdc)3}4{Co2(na)4(LT)2}3] containing the desired dicobalt cluster was obtained, giving extraordinarily high electrocatalytic oxygen evolution activity in water at pH = 13 with overpotential as low as 225 mV at 10.0 mA cm–2.